The People Are The Mouth Of Creation - The Source Of Spirituality - Qurbanova Muqaddas Omonovna; Hasanov Nurmuhammad Heydarali Ogli (Genius Journals, 2023)
In this article, the ancestors of the current Uzbek people lived several thousand years ago, and they had a long and difficult way to create a high and unique culture, the formation of unique cultural traditions in the regions where these people lived, the first simple desires of the ancient people, dreams it is thought that their hopes and qualities are a unique source of education and spirituality in ancient epics.
Keywords: Uzbek; people; ancestors